Membangun Pemahaman Karakter Kejujuran Melalui Permainan Tradisional pada Anak Usia Dini di TK Al-Urwatul Wutsqo - Selly Aprilia Santana (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
Honesty is a fundamental life value that must be taught to early childhood. Teaching children to always say, behave and behave honestly will be a useful lesson for their life in the future. Instilling honesty from an early age will generally be more easily absorbed and instilled by children into a good habit until they are adults. The application of an honest attitude in the life of early childhood is very necessary and needed in everyday life because an honest attitude is a good and commendable attitude. Honesty is needed in various aspects of life. At Al-Urwatul Wutsqo Kindergarten, teachers make learning methods through traditional games to build understanding of children's honesty character.